The volatility curse: revisiting the paradox of plenty - Frederick van der Ploeg; Steven Poelhekke (Center for Economic Studies and ifo Institute (CESifo), 2009)
The volatility of unanticipated output growth in income per capita is detrimental to long-run development, controlling for initial income per capita, population growth, human capital, investment, openness and natural resource dependence. This effect is significant and robust over a wide range of specifications. We unravel the effects of volatility by opening the black box and conditioning the variance of growth shocks on several country characteristics. Natural resource dependence, physical and institutional barriers to trade and associated policy shocks increase volatility sharply and harm growth through this indirect channel. The robust indirect effect of natural resources through volatility trumps any direct effects on economic development, even if natural resource dependence is measured net of extraction costs. Financial development appears to mitigate the harmful causes of volatility. Our panel data estimation confirms our cross-country results, but we also offer evidence that well developed financial systems amplify the effect of short-term terms-of-trade volatility on macroeconomic volatility.
Keywords: C12; C21; C23; F43; G20; O11; O41; Q32; 330; volatility; growth; resource curse; financial development